2018
DOI: 10.1155/2018/2045629
|View full text |Cite
|
Sign up to set email alerts
|

Avian Community Structure as a Function of Season, Habitat Type, and Disturbance, in Mole National Park, Northern Region (Ghana)

Abstract: The study assessed factors that influenced bird-habitat preference, diversity, and spatial distribution in Mole National Park. Birds were identified using point count sampling method, while ordination techniques were performed to determine the influence of environmental factors on bird-habitat preference. A total of 4951 individuals belonging to 131 species were identified across the four habitat types in the wet (n = 3033) and dry (n = 1648) seasons. Despite the high abundance and richness of birds in the woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
2
8
0
1
Order By: Relevance
“…Farmland and uncultivated grassland differed significantly from the gallery forest. This is in line with the findings of Ajagbe (2004) and Nsor et al (2018) that reported that avian community structure is a function of habitat types as well as other factors. The availability of crops and type of crops grown on farmlands could also have a marked effect on bird's abundance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Farmland and uncultivated grassland differed significantly from the gallery forest. This is in line with the findings of Ajagbe (2004) and Nsor et al (2018) that reported that avian community structure is a function of habitat types as well as other factors. The availability of crops and type of crops grown on farmlands could also have a marked effect on bird's abundance.…”
Section: Discussionsupporting
confidence: 93%
“…These requirements make them more sensitive to changes in the environment causing them to easily disappear or get disturbed when the habitat is destroyed or degraded (Bird life International 2000). Habitat selection and use by birds has been long established as functional field of study in bird ecology Nsor et al (2018). Studies on habitat selection have revealed that several factors such as land scape structure, nest predation, competition, intraspecific attraction, food availability, variable climate, diseases and human activities can influence animals' freedom while traversing a landscape in search of suitable habitats (Nsor et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Agyei-Ohemeng et al [82] and Nsor et al [83] in the MNP found similar results that are corroborated by our current study in further assessment of the functional diversity of the avifauna community in the park. Elsewhere in Africa, Mengesha et al [84] recorded the highest bird species diversity in the riverine woodland habitats during the wet season, attributing it to the availability of water and food variety.…”
Section: Variations In Species and Functional Diversity Measuressupporting
confidence: 93%
“…community ecology relates habitat heterogeneity to avian species diversity (Tews et al, 2004). Birds always inhabit specific habitats and vegetation structure affects their composition and structure (Caziani & Derlindati, 2000;Brawn et al, 2001;Gabbe et al, 2002;Seymour & Simmons, 2008;Earnst & Holmes, 2012;Nsor et al, 2018).…”
mentioning
confidence: 99%